Hydrogen sensing performance of a nickel oxide (NiO) thin film-based device. (5th January 2015) - Chou, Po-Cheng; Chen, Huey-Ing; Liu, I-Ping; Chen, Chun-Chia; Liou, Jian-Kai; Hsu, Kai-Siang; Liu, Wen-Chau
Abstract An interesting nickel oxide (NiO) thin film-based hydrogen sensor device, prepared by a low-powered (50 W) radio-frequency (RF) sputtering process, is studied and demonstrated. The studied device shows improved performance including a very high hydrogen sensing response ratio (416 (ΔR/R)), an extremely low detecting limit (<50 ppm H2/air), a high sensing response speed (7 s), a lower operating temperature (≦350 °C) and a widespread sensing range of hydrogen concentration (50–10, 000 ppm H2/air). In addition, the device demonstrates benefits of low cost, easy fabrication and chemical stability. Based on these advantages, therefore, the studied NiO thin film sensor device shows promise for high-performance hydrogen sensing applications.